JEMBATAN BOX GIRDER SEGMENTAL - Johanes B. Borsak P. Sitanggang; Nova Arstriyanto; Himawan Indarto; Parang Sabdono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Box girder bridge in Indonesia, including new. The intent and purpose of this thesis is to plan the bridge box girder structure. Where bridges with spans plan along 310 m with 2 pillars and different pillar heights. Because there are differences in the height of this bridge inspected by stiffnes balance method to locate deviation and shakes the same time so strong pillar and not collapse. Planning earthquake loads based on the latest regulations (SNI 03-2833-2008 Earthquake Resistance Evaluation Standards for Bridge). Analysis of bridge structures using SAP program. The bottom structure which includes abutment and foundation broom method to determine the shear boundary. The conclusion that can be drawn is necessary to balance stiffnes to know the exact dimensions of the pillars of that bridge is on it can stand firmly. Plastic hinge to determine the maximum acceptable shear pillar and foundation to determine the shear foundation failure not to occur, which can lead to the destruction of the structure.